EDUKASI KESEHATAN MELALUI VIDEO SEBAGAI UPAYA ANTISIPASI COVID-19 DI DESA PANDANSARI LOR - Primasa Minerva Nagari; Okky Irwina Savitri; Ari Hakim Putra; Devi Sandra Anggraeni; Akbar Aldi Surya Nugraha (Universitas Muhammadiyah Malang, 2021)
The emergence of the Corona-19 Virus Disease Pandemic encourages the importance about socialization about health educating and raising public awareness about clean and healthy lifestyles. The community needs to know how to avoid Covid-19 so that it does not becomean epidemic in around Pandansari Lor Jabung Village, Malang Regency. The health education video is a practical tool that can be used to promote Covid-19 participation. The purpose of community service is talkable assistance that is easily understood and understood to be healthy and healthy living in Pandansari Lor Jabung Village, Malang Regency to encourage the outbreak of Covid-19. The activity stage was planned for 2 weeks, which was preceded by coordination and communication with the Pandansari Lor village. This socialization is presented in the form of a video which contains health education about clean and healthy lifestyles which contains sports tutorials (gymnastics) at home, hand washing tutorials according to standards of WHO (World Health Organization), tutorials on making and using disinfectants at home, and tutorials on making herbal medicine to increase body immunity. So that through the educational videos provided can be understood well by the community.